## What is the solution to the equation x^2 + 2x – 3 = 0?

To solve the equation x^2 + 2x - 3 = 0, we can use the quadratic formula: x = (-b ± √(b^2 - 4ac)) / (2a) In this equation, a,…

Skip to content
# math

##
What is the solution to the equation x^2 + 2x – 3 = 0?

To solve the equation x^2 + 2x - 3 = 0, we can use the quadratic formula: x = (-b ± √(b^2 - 4ac)) / (2a) In this equation, a,…

##
If 2a=5b=6c, then what is the value of a:b:c?

Given that 2a = 5b = 6c, we can set up ratios to find the value of a:b:c. Let's start by equating pairs of these ratios: 2a = 5b ⇒…